2022
DOI: 10.15632/jtam-pl/143606
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grouting pressure volatility on additional response of adjacent pile foundation in shield construction

Abstract: Soil parameters along the heading direction are subjected to spatial variability during shield construction, so grouting pressure requires constant adjustment to ensure ground stress stability. This causes grouting pressure to fluctuate around the design pressure/curve. Therefore, the influence of the grouting pressure volatility on the adjacent loaded-pile foundation should be considered in shield tunneling. In this study, a refined numerical simulation of the shield construction process is conducted using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It was found that the settlements of pile foundation and pile perimeter soil surface were closely related to the relative position between piles and tunnels, and the pile perimeter soil settlement was mainly responsible for the pile foundation tilting (Boonyarak et al, 2014;Dias et al, 2015;Wang et al, 2018). Moreover, factors such as pile top load, ground loss, soil strength, grouting pressure, pile size, and tunnel diameter were considered as the dominant factors of the internal stress and deformation of pile foundation (Lee, 2013;Liu et al, 2014;Huang et al, 2021;Al-Omari et al, 2019;Jeon et al, 2020;Ayasrah et al, 2021;Zhang et al, 2022). Furthermore, it was investigated that the isolation pile reinforcement can strengthen the whole pile foundation, it had obviously better reinforcement effect than grout reinforcement and longeron cross bracing reinforcement (Park et al, 2015;Li et al, 2020;Lv et al, 2020;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the settlements of pile foundation and pile perimeter soil surface were closely related to the relative position between piles and tunnels, and the pile perimeter soil settlement was mainly responsible for the pile foundation tilting (Boonyarak et al, 2014;Dias et al, 2015;Wang et al, 2018). Moreover, factors such as pile top load, ground loss, soil strength, grouting pressure, pile size, and tunnel diameter were considered as the dominant factors of the internal stress and deformation of pile foundation (Lee, 2013;Liu et al, 2014;Huang et al, 2021;Al-Omari et al, 2019;Jeon et al, 2020;Ayasrah et al, 2021;Zhang et al, 2022). Furthermore, it was investigated that the isolation pile reinforcement can strengthen the whole pile foundation, it had obviously better reinforcement effect than grout reinforcement and longeron cross bracing reinforcement (Park et al, 2015;Li et al, 2020;Lv et al, 2020;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%